Circuit training on VO2max physical condition: How does it affect handball athletes? - Ardian, Roy; Dewantara, Julian; Shareef, Qays Banwan (Journal of Applied Movement and Sport Science, 2025)
Background Handball is an intermittent, high-intensity sport that demands sustained aerobic capacity to maintain optimal performance during training and competition. Adequate VO2max levels are therefore essential for athletes to cope with repeated bouts of explosive movement and prolonged physical exertion. Objectives This study aimed to examine the effectiveness of a circuit training method in improving physical condition, specifically VO2max levels, among handball athletes. Methods An experimental one-group pretest–posttest design was employed. The participants consisted of 15 athletes from the Sambas district handball team, aged 20–25 years, selected through purposive sampling. The athletes completed a structured circuit training program implemented across 12 sessions with a frequency of three sessions per week. VO2max was assessed before and after the intervention using the Yo-Yo Intermittent Recovery Test Level 1. Data were analyzed using SPSS 26. Results The findings revealed a significant improvement in VO2max following the circuit training program, with a significance value of 0.000 (< 0.05). These results indicate that circuit training is effective in enhancing aerobic capacity among handball athletes Conclusion Circuit training provides a substantial positive impact on VO2max development in handball players, supporting its use as a conditioning strategy to improve overall physical performance. This study contributes empirical evidence on the effectiveness of circuit-based conditioning for intermittent sports. The results offer practical insights for coaches and sport practitioners in designing targeted training programs aligned with the physiological demands of handball athletes.